Demography and homing behavior in the poorly-known Philippine flat-headed frog Barbourula busuangensis (Anura: Bombinatoridae) - Marta Miñarro; Patricia Burrowes; Claudia Lansac; Gregorio Sánchez-Montes; Leticia E. Afuang; Ignacio De la Riva (PeerJ)
The flat-headed frog, Barbourula busuangensis, is a poorly known, riverine species, endemic to the province of Palawan in the Philippines. We applied capture-mark-recapture (CMR) methods to follow individuals at two sites (Malbato and San Rafael) in the island of Busuanga over 10 months in 2022–2023. We used passive internal transponders (PITs) to mark adult and subadults and single-colored visual internal elastomers (VIEs) for cohorts of juveniles. From a total of 196 frogs PIT-tagged in Malbato and 144 in San Rafael, we obtained overall recapture rates of 49% and 60% respectively. We used the POPAN formulation in MARK software to estimate abundance, survival, movement, and age-class demographics. Our best model estimated an average population size of 268 frogs at Malbato and 232 at San Rafael, and constant survival probabilities (mean ≥ 0.97) at both sites. When adding age classes to the model, abundance of adults was always higher than that of subadults producing an age structure dominated by adults at both sites. Growth rates decreased significantly with body size, being higher in juveniles (1.51 mm/month) and subadults (1.56 mm/month) than in adult frogs (0.60 mm/month). At these growth rates frogs may reach adulthood at 2.5 years, with the oldest individuals likely being over 11 years old. CMR data confirmed site fidelity, and translocation experiments revealed that frogs have the ability to home when displaced 10–50 m upstream and downstream from their original capture site. This is the first long-term study of B. busuangensis using robust field and analysis methods. Our data suggest that B. busuangensis is stable at present in Busuanga, with long-lived adults and dispersing subadults. We expect that these data may serve as baseline of current population abundance, age structure and growth rates which are factors that tend to be affected when species are threatened. In this way it may help researchers and conservation practitioners detect potential changes that may occur as this species confronts the challenges of the Anthropocene.